Analysis and Study of Coriandrum Sativum Linn as a Promising Component - Mulpuri, Gowtham (Journal of Research in Science and Engineering, 2024)
Coriander (Coriandrum sativum L.), is a versatile plant associated with the Apiaceae family. It is known as spice which is very popular in India and also used in culinary (leaves called cilantro) like salads, salsas, garnishes, etc. The whole coriander herb, with its abundance of Phytochemical, has a variety of pharmacological qualities that extend beyond its use in cooking. Significant attention has been paid to the potential benefits of coriander essential oil and linalool, two particular chemicals that have been discovered to be effective in treating ulcers and colitis. This review provides an overview of coriander's chemical constituents, cultivation, traditional uses, and potential side effects. The entire coriander herb is employed in treating illnesses by managing biomarkers such as myeloperoxidase (MPO), stool consistency, ulcer severity, and similar indicators. Together with India, Morocco, Romania, France, Spain, Italy, the Netherlands, Myanmar, Pakistan, Turkey, Mexico, Argentina, South and Western Australia and to a lesser extent the UK and USA are among the countries where coriander is commercially grown. Additionally well - known for their therapeutic qualities. Coriander is therefore frequently used as a component in the making of Ayurvedic medications.